Home palliative care professionals perception of challenges during the Covid-19 outbreak: A qualitative study. (May 2021) - Franchini, Luca; Varani, Silvia; Ostan, Rita; Bocchi, Ilenia; Pannuti, Raffaella; Biasco, Guido; Bruera, Eduardo
Background: Home palliative care services have played an essential role during the first wave of the SARS-CoV-2 outbreak by providing symptom control, drug procurement, and psychological support for frail patients and their families unable to leave their homes. Aim: To understand how home palliative care professionals were affected by the outbreak, describing changes and challenges in their daily work as well as their reactions to the Covid-19 pandemic in Italy. Design: Qualitative study conducted using telephone semi-structured interviews, with thematic analysis. Setting/participants: Thirty home care professionals working for an Italian non-profit organization which provides home palliative care for cancer patients and their families. Results: Three main themes were identified. The first theme showed both patient-related and practice-related challenges participants faced in their daily work, requiring the implementation of different communication methods and patient and family education on risk prevention. The second theme showed the perception of increased responsibility and being the only landmark for family played a decisive role in participants' positive attitude. The third theme highlighted the participants' perception of the critical role of a home care setting in this emergency situation. Conclusions: The first wave of the Covid-19 pandemic brought many challenges and stressors for home palliative care professionals. On the other side, they reported a satisfaction with their critical role in carrying out their work with patients at risk.